Functional traits of the gut microbiome correlated with host lipid content in a natural population of Drosophila melanogaster. (26th February 2020) - Kang, David; Douglas, Angela E.
Abstract : Most research on the nutritional significance of the gut microbiome is conducted on laboratory animals, and its relevance to wild animals is largely unknown. This study investigated the microbiome correlates of lipid content in individual wild fruit flies, Drosophila melanogaster . Lipid content varied 3.6-fold among the flies and was significantly correlated with the abundance of gut-derived bacterial DNA sequences that were assigned to genes contributing to 16 KEGG pathways. These included genes encoding sugar transporters and enzymes in glycolysis/gluconeogenesis, potentially promoting sugar consumption by the gut microbiome and, thereby, a lean fly phenotype. Furthermore, the lipid content of wild flies was significantly lower than laboratory flies, indicating that, as for some mammalian models, certain laboratory protocols might be obesogenic for Drosophila . This study demonstrates the value of research on natural populations to identify candidate microbial genes that influence ecologically important host traits.